The supplemental nutrition assistance program and older adults: A scoping review protocol - Jessica Soldavini (PLoS ONE, 2025)
Objective The objective of this scoping review is to describe the scope of original published research on SNAP and older adults. Introduction Food insecurity among older adults in the United States is a significant public health issue. Participation in the Supplemental Nutrition Assistance Program (SNAP), the largest nutrition assistance program in the United States, by older adults is lower than the overall participation rate. Inclusion criteria This scoping review will include original research focused on older adults (aged 60 years and older) and participation in SNAP. Studies should address at least one of the following: examining one or more outcomes related to participation in SNAP, facilitators or barriers to SNAP participation, and/or evaluation of a program, policy or other strategy for influencing SNAP participation. Methods Databases to be searched include PubMed, Scopus, CINAHL, and ProQuest. Sciwheel will be used for deduplicating references that will be imported into Covidence for screening and extracting data. Two independent reviewers will screen titles/abstracts followed by full-text articles to assess whether articles meet inclusion criteria and then complete a data extraction template for each included article. A third reviewer will resolve any discrepancies. The findings will be summarized and presented in tables and narrative form.